(untitled) (Experimental biology, 2017)
The investigated strains of lactic acid bacteria are more sensitive to bile than in a low pH value. Most sensitive to bile cultures were L. plantarum 22, L. brevis B-3, L. plantarum 2b, and 14d. Adapted to the low pH value of culture L. brevis B-3 and L. plantarum 22 were more resistant to bile compared with baseline. The most resistant to bile cultures are L. fermentum 27 and P. shermanii.